Advances in ELISA-based detection of equine leptospirosis - Thayná Laner Cardoso; Daniela Rodriguero Wozeak; Isabel Ladeira Pereira; Laura Dias da Silva Ribeiro; Rogério Oliveira Rodrigues; Daiane Drawanz Hartwig (Brazilian Journal of Microbiology, 2026)

Olfactory responses of Philaenus spumarius nymphs to plants from field margins of Mediterranean perennial crops - Raquel Dias-Pereira; Nuno Rodrigues; José Alberto Pereira; Isabel Rodrigues (Crop Protection, 2026)

Ractopamine under dietary protein adjustment improves growth performance and carcass traits of immunocastrated and surgically castrated pigs slaughtered 21 days after vaccination - Diego Duran Araujo; Matheus de Almeida Ferreira; Lucas Alves Rodrigues; Idael Matheus Góes Lopes; Marcelo Dourado de Lima; Luíza de Almeida Ramos; Rafaela Jorge Sarsur de Freitas Ribeiro; Hemille Antunes Ferreira Miranda; Isabel Luísa Ribeiro de Abreu Teixeira; Francisco Carlos de Oliveira Silva; Walter Motta Ferreira; Dalton de Oliveira Fontes (Tropical Animal Health and Production, 2026)
The objective of this study was to evaluate the effects of immunocastration and ractopamine hydrochloride (RAC) supplementation on growth performance and carcass traits of male pigs slaughtered 21 days after the second immunization. Sixty-four pigs (Landrace × Large White, initial body weight 103.05 ± 0.67 kg) were individually tagged and randomly assigned to a 2 × 2 factorial arrangement in a completely randomized design, consisting of two castration methods (immunocastrated vs. surgically castrated) and two dietary RAC levels (0 or 10 ppm). No castration method × RAC interactions were observed for any variable ( P > 0.05). Immunocastrated (IM) pigs exhibited 19.5% greater average daily gain (ADG) and 13% lower feed-to-gain ratio (FG) compared with surgically castrated (SC) pigs ( P < 0.05). IM pigs also showed reduced backfat thickness across all measurement sites and greater lean meat percentage, whereas SC pigs had higher carcass yield ( P < 0.05). Ractopamine supplementation under increased amino acid supply increased ADG by 13.6%, improved hot carcass weight by 3.1%, and reduced FG by 13% ( P < 0.05). Overall, immunocastration improved growth performance and carcass leanness, while RAC supplementation increased average daily gain by 13.6%, confirming its additive effect under a shortened 21-day post-immunization interval. Immunization against GnRH combined with RAC feeding represents an effective strategy for producing heavy-weight finishing pigs with improved efficiency.

Plinia peruviana (Poir.) Govaerts (jabuticaba) extract inhibits the development of gastric ulcers in animal models through gastroprotective mechanisms - Isabel Sousa Alcântara; Renata Torres Pessoa; Lucas Yure Santos da Silva; Roger Henrique Souza da Costa; Aparecida Barros da Silva; Tarcisio Mendes Silva; Samara Alves Brito; Anita Oliveira Brito Pereira Bezerra Martins; Jean Carlos Pereira Sousa; Andréa Rodrigues Chaves; Ricardo Neves Marreto; Francisco Sandro Menezes Rodrigues; et al. (Food Bioscience, 2026)

Adaptive mechanism of the Azul genetic group goats: Heat exchange - Neila Lidiany Ribeiro; Edilson Paes Saraiva; Maria Norma Ribeiro; Jaciara Ribeiro Miranda; Maria Isabel Gomes de Lima; Dermeval Araújo Furtado; Neriane Rodrigues de Lima; Roberto Germano Costa (Small Ruminant Research, 2026)

Caffeine removal and degradation in sanitary sewage: Insights into microbial shifts and methane yield - Rômulo Mota Teixeira; Caroline Varella Rodrigues; Carolina Nemeth Comparato; Eduardo Lordelo Volpato; Guilherme Martins Grosseli; Isabel Kimiko Sakamoto; Maria Bernadete Amâncio Varesche (Journal of Water Process Engineering, 2026)

Highly efficient (MFe)zeolite catalysts for nimesulide degradation via Fenton-type oxidation - Carmen S.D. Rodrigues; Susana Costa; Olívia S.G.P. Soares; António M. Fonseca; Pier Parpot; Manuel F.R. Pereira; Luis M. Madeira; Elisabetta Rombi; Isabel C. Neves (Chemical Engineering Journal, 2026)

Influence of non-host aromatic plants on the survival and olfactory behavior of the African citrus psyllid, Trioza erytreae - Jaciley Bragança-Costa; Daniela Ruano; Nuno Rodrigues; Alberto Fereres; José Alberto Pereira; Isabel Rodrigues (Journal of Pest Science, 2026)
Trioza erytreae Del Guercio, 1918, commonly known as the African citrus psyllid, is one of the main vectors of Huanglongbing (citrus greening), the most destructive citrus disease worldwide. Currently, there is no effective treatment for HLB; therefore, management efforts primarily focus on controlling the insect vectors. This often involves the use of insecticides, which raises concerns about environmental impact and the development of insecticide resistance. This study evaluates the potential of five aromatic non-host plants commonly found in the Mediterranean basin, which overlap with regions of citrus production ( Cistus ladanifer , Rosmarinus officinalis , Foeniculum vulgare , Lavandula stoechas , and Thymus mastichina ) to influence the survival and olfactory behavior of T. erytreae . Although the psyllids were able to survive for several days on these non-host plants, survival was significantly lower compared to the citrus host ( Citrus limon ), with C. ladanifer having the most detrimental effect. Olfactory assays revealed that, in females, C. limon , C. ladanifer , and L. stoechas elicited significantly higher probabilities of attraction compared with R. officinalis and T. mastichina . In males, C. limon elicited a significantly higher probability of attraction than R. officinalis , T. mastichina , and L. stoechas . A total of 123 volatile organic compounds (VOCs) were identified across all plant species, of which 48 were found to be important for the olfactory response of T. erytreae . Among these, 19 VOCs were positively correlated with psyllid attraction, while 15 showed negative correlations, indicating a potential repellent or disruptive effect. These results suggest that specific VOCs emitted by aromatic non-host plants can modulate host-seeking behavior in T. erytreae , highlighting their potential application in the development of semiochemical-based, environmentally sustainable strategies for citrus pest management.

Machine learning in estimating the weight of Tilapia Oreochromis niloticus juveniles - Lessandro do Carmo Lima; Adriano Carvalho Costa; Heyde Francielle do Carmo França; Alene Santos Souza; Gidélia Araújo Ferreira de Melo; Brenno Muller Vitorino; Vitória de Vasconcelos Kretschmer; Isabel Rodrigues de Rezende; Rafael Vilhena Reis Neto (Aquaculture, 2026)

Mechanical traumatic injuries as a cause of death in free-ranging neotropical non-human primates living in anthropogenic matrices - Rafaela Magalhães Barros; Isabel Luana de Macêdo; Davi Emanuel Ribeiro de Sousa; Yasmin Nunes Godoy da Fonseca; Liz de Albuquerque Cerqueira; Gabriela Rodrigues de Toledo Costa; Liria Queiroz Luz Hirano; Márcio Botelho de Castro (Primates, 2026)
Traumatic injuries are a major cause of morbidity and mortality in free-ranging non-human primates (NHPs), often associated with anthropogenic pressures such as habitat loss, urbanization, and interactions with domestic animals. This study characterized some epidemiological, spatial, and pathological patterns of mechanical traumatic injuries in free-ranging non-human primates from anthropogenically altered areas of the Federal District. Of 696 necropsies performed, 215 cases (30.9%) involved mechanical trauma. Black-tufted marmosets ( Callithrix penicillata ) were the most affected species (90.2%), followed by capuchins ( Sapajus libidinosus , 6.5%) and howler monkeys ( Alouatta caraya , 3.3%). Adults were more frequently affected than juveniles, with no sex-related differences. Blunt trauma accounted for the majority of cases (82.3%), most commonly as polytrauma, with cranial involvement in 65.2% of animals. Carnivore predation was the leading cause of blunt-penetrating trauma (89.4%), while gunshot injuries were rare. Bone fractures were identified in 65.1% of cases, most often involving the skull and long bones, and internal injuries were frequent in the thoracic and abdominal cavities. These findings demonstrate that mechanical trauma represents a critical threat to NHPs in urban and peri-urban areas, where exposure to human infrastructure and domestic animals is heightened. The results underscore the need for mitigation strategies to reduce mortality and support the conservation of free-ranging primate populations in human-dominated landscapes.

ProAKAP4 as a protein marker of sperm quality: Insights from frozen-thawed ejaculated and epididymal sperm - Myrian Megumy Tsunokawa Hidalgo; Ana Beatriz Marques de Almeida; Leticia Amanda dos Santos Silva; Vinicius Wagner Silva; Julia Rodrigues Greghi; Natália Ribeiro Sambatti; Luiz Guilherme Corsi Trautwein; Rodrigo Yudi Palhaci Marubayashi; João Carlos Pinheiro Ferreira; Maria Isabel Mello Martins (Theriogenology, 2026)

Economic benchmarking of assisted pollination methods for kiwifruit flowers: Assessment of cost-effectiveness of robotic solution - Isabel Pinheiro; Pedro Moura; Leandro Rodrigues; Abílio Pereira Pacheco; Jorge Teixeira; António Valente; Mário Cunha; Filipe Neves dos Santos (Agricultural Systems, 2026)

Reliable identification of flood-borne deposits in speleothems using magnetic microscopy - Samuel L. Piascik; Roger R. Fu; Nicolás M. Stríkis; Ricardo I.F. Trindade; Julio Cauhy Rodrigues; Francisco W. Cruz; Gelson F. Souza-Junior; Andrea Borsato; Vitor Azevedo; Plinio Jaqueto; Isabel Tamara Pedron; Perri Thaler; et al. (Quaternary Science Reviews, 2025)

Synbiotic administration improves systemic and vascular alterations in rats with experimental microsurgical extrahepatic cholestasis: role of perivascular mesenteric innervation - Pablo Méndez-Albiñana; Laia Cros-Brunsó; Raquel Rodrigues-Díez; Pilar Rodríguez-Rodríguez; Luis Santamaría; Ana Muñoz-Labrador; Teresa Requena; Laura Casani; Francisco Félix Caballero; Ma Isabel Prieto-Nieto; Mar Villamiel; Javier Blanco-Rivero (Bioactive Carbohydrates and Dietary Fibre, 2025)

Seasonal olfactory response of Philaenus spumarius (Hemiptera: Aphrophoridae) towards traditional Portuguese olive cultivars - Isabel Rodrigues; Jacinto Benhadi-Marín; Nuno Rodrigues; Paula Baptista; José Alberto Pereira (Crop Protection, 2025)

Stability of lutein-based nanoemulsions under thermal and UVC-light exposure: Effect of lutein esterification and oil phase constitution - Maria Isabel Ordoñez Lozada; Daniele Bobrowski Rodrigues; Iriani Rodrigues Maldonade; Talita de Almeida Fernandes; Ernandes Rodrigues de Alencar; Lívia de Lacerda de Oliveira (Food Chemistry, 2025)

Cymbopogon winterianus essential oil as an alternative source for producing terpenic esters with potential plant-protective antifungal activity using lipase immobilized on a lignin composite - Carlos Alberto Chaves Girão Neto; Carolin Richter; Isabel Cristina Medeiros Prasilde; Kirley Marques Canuto; Magda Elisa Turini da Cunha; Bruno M. Moerschbacher; Tigressa Helena Soares Rodrigues; Maria Valderez Ponte Rocha (Biocatalysis and Agricultural Biotechnology, 2025)

Optimistic climate mitigation scenario halves projected range loss in a neotropical dolphin - Rodrigo Tardin; Guilherme Maricato; Jeremy J. Kiszka; Mauricio Cantor; Israel Maciel; Gabriel Melo-Santos; Laura May-Collado; Ana Carolina Meirelles; Maria Isabel C. Gonçalves; Fábio G. Daura-Jorge; Renata S. Sousa-Lima; Yvonnick Le Pendu; et al. (Ocean & Coastal Management, 2025)

The GreenValue project: exploring salt tolerant plants as sources of innovative food additives - Célia Quintas; Isabel Ratão; Catarina G. Pereira; Maria J. Rodrigues; Luísa Custódio (Phytochemistry Letters, 2025)

Protection and safety of aluminum hydroxide adjuvant and chimeric antigen containing predicted epitopes from bacteria murC gene in Aeromonas hydrophila fish infection - Jojo Silva Rodrigues; Maria Roméria da Silva; Camila Aparecida Martins; Laura Alves Zuanon; Karina Ventura Boechat Martins; Pedro Segantini Tótola; Jheneze Guimarães Pereira Rocha; Mariana Grôppo Parma; Isabel Samila Lima Castro; Tarciza Fernandes Nascimento; Allan Rodrigues Pires; Filipe Silveira Azevedo; et al. (Fish & Shellfish Immunology, 2025)

Decision Model for Sustainable Urban Drainage Systems: A Technical, Social, and Economic Multicriteria Analysis - Izabel Rodrigues Leite; Sharon Kelly de Melo; Luiz Felipe Finck; Ana Julia Motyczka Finck; Aleska Kaufmann Almeida; Isabel Kaufmann de Almeida (Water Resources Management, 2025)

The role of nest-site interference competition with Cape Verde Shearwater in explaining breeding success of Red-billed Tropicbird on Raso Islet, Cape Verde archipelago - Jaime A. Ramos; Catelene Monteiro; Isabel Rodrigues; Diana M. Matos; Vitor H. Paiva; Filipe R. Ceia; Jorge M. Pereira; Kenny Delgado; Stefan Antunes (Journal of Ornithology, 2025)

Temporal dynamics of class 1 and class 3 integron pools in treated wastewater - Rafael D.S. Tavares; Elsa T. Rodrigues; Marta Tacão; Isabel Henriques (Water Research, 2025)

Phytochemical diversity and biological activities of Hypericum japonicum and Hypericum sampsonii: potential for natural product-based food applications - Paula Barciela; Daniele B. Rodrigues; Ana Perez-Vazquez; Tayse F.F. da Silveira; Tânia C.S.P. Pires; Filipa Mandim; Maria Carpena; Carla Pereira; Isabel C.F.R. Ferreira; Lillian Barros; Miguel A. Prieto (Food Chemistry, 2025)

Biochemical biomarker profiles of different organs of Phrynops geoffroanus freshwater turtle (Testudines, Chelidae) reveal pollutant effects from an anthropized aquatic environment - Maria Isabel Afonso da Silva; Daína Lima; Larissa Paola Rodrigues Venancio; Tiago Lucena da Silva; Claudia Regina Bonini Domingos; Eduardo Alves de Almeida (Environmental Research, 2025)

COVID-19 pandemic exacerbated food insecurity in South American countries - Carlos Frederico A. Vasconcelos-Neto; Michelle Jacob; Daniel Tregidgo; Denis Valle; Hani R. El Bizri; Sávio Marcelino Gomes; Julia E. Fa; Thais Q. Morcatty; Frederico Ozanan Barros Monteiro; Alessandra Scofield; Alessandra Matte; Willandia A. Chaves; et al. (Food Security, 2025)
The COVID-19 pandemic triggered unparalleled political, economic, and social ramifications, exacerbating global food insecurity (FI). To understand the overall impact of the pandemic and how different socio-economic groups were affected, we assessed prevalence and severity of FI in a sample of 18,997 households across seven countries in South America. We employed the Food Insecurity Experience Scale developed by the FAO. Our results showed that pre-pandemic, 4.5% of the sampled population across the entire continent faced Moderate FI, while 0.6% experienced severe FI. During the pandemic, Moderate FI increased to 16.9% (+ 12.4%), and Severe FI to 2.7% (+ 2.1%). By country, pre-pandemic households in Venezuela had the highest prevalence of Moderate FI (9.7%), with Peru experiencing the highest Severe FI frequency (1.1%). Peru had the greatest rise in Moderate (+ 23.9%) and Severe FI (+ 4.6%) during the pandemic. Low-income households, defined as those earning < 2 minimum wages per month, were most susceptible to FI. Uruguayan low-income families exhibited the most significant rise (+ 40.4%) in Moderate FI, while those in Peru experienced an increase of + 9.1% in Severe FI. This study measures the profound and far-reaching impact of the COVID-19 pandemic on FI in South America. Our findings also emphasise the critical importance of implementing effective public policy interventions to improve resilience against future shocks. This would enable policymakers to develop targeted strategies that address the immediate challenges posed by pandemics as well as laying the groundwork for a more resilient and sustainable food security landscape in the region.

Modeling and spatio-temporal prediction rainfall data applied to mass movements in Belo Horizonte, Minas Gerais - Brazil - Bianca Nespoli Cortez; Jandresson Dias Pires; Gabrielle Ferreira Pires; Gérson Rodrigues Dos Santos; Marcos Barreto De Mendonça; Eduardo Antonio Gomes Marques; Nathan Ribeiro Mac Laren Nogueira; Isabel Eustáquia Queiroz Volponi (Journal of South American Earth Sciences, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Acoustic wave propagation in oil wells: A comparison between semi-analytical and finite element modeling approaches - Luis Paulo Brasil de Souza; Juan Andrés Santisteban Hidalgo; Tiago de Magalhães Correia; Isabel Giron Camerini; Guilherme Rezende Bessa Ferreira; Antônio de Souza Rodrigues; Alan Conci Kubrusly; Arthur Martins Barbosa Braga (Wave Motion, 2025)

Antifungal resistance in yeasts from One Health perspective: A Brazilian study - Rafael Wesley Bastos; Nalu Teixeira de Aguiar Peres; Kássia Jéssica Galdino da Silva; Ludmila Gouveia Eufrasio; Daniel Santana de Carvalho; Gabriela Silva Cruz; Fabíola Lucini; Lorena Souza Silva; Sthefany Emanuelle Silva; Hareton Teixeira Vechi; Manoella do Monte Alves; Luciana Rodrigues Ferreira Ribeiro; et al. (Science of The Total Environment, 2025)

Two-stage versus single-stage anaerobic co-digestion on methane synthesis: Energy prospects and microbial community - Kauanna Uyara Devens; Alexandre Rodrigues Ribeiro; Franciele Pereira Camargo; Isabel Kimiko Sakamoto; Maria Bernadete Amâncio Varesche; Edson Luiz Silva (Process Safety and Environmental Protection, 2025)

Fire management benefits tree growth and survival in the Brazilian savanna - Samuel da Rocha Montenegro; Maxmiller Cardoso Ferreira; Ana Carla dos Santos; Clara Baringo Fonseca; Cassy Anne Rodrigues; Isabel Belloni Schmidt (Journal of Environmental Management, 2025)

Valorization of natural resources - development of a functional plant-based beverage - Filipa A. Fernandes; Custódio Roriz; Ricardo C. Calhelha; Paula Rodrigues; Tânia C.S.P. Pires; Miguel A. Prieto; Isabel C.F.R. Ferreira; Lillian Barros; Sandrina A. Heleno (Food Chemistry, 2025)

Effects of Amendments on Tropical Mining Soils: Geochemical, Toxicological and Microbiological Approaches - Jacqueline Zanin Lima; Jéssica Pelinsom Marques; Isabel Kimiko Sakamoto; Eduardo Ferreira da Silva; Valéria Guimarães Silvestre Rodrigues (Water, Air, & Soil Pollution, 2025)

Insights of energy potential in thermophilic sugarcane vinasse and molasses treatment: does two-stage codigestion enhance operational performance? - Alexandre Rodrigues Ribeiro; Kauanna Uyara Devens; Franciele Pereira Camargo; Isabel Kimiko Sakamoto; Maria Bernadete Amâncio Varesche; Edson Luiz Silva (Biodegradation, 2025)

Effect of Solid-Fermented Brewer’s Spent Grain on Growth, Metabolism, and Oxidative Status of European Seabass (Dicentrarchus labrax) - Tássia Estevão-Rodrigues; Helena Fernandes; Sara Moutinho; Marta Ferreira; Carolina Castro; Isabel Belo; José Manuel Salgado; Aires Oliva-Teles; Helena Peres (Fishes, 2025)
Replacing traditional agricultural ingredients with biotechnologically improved agro-industry by-products in fish diets promotes sustainable aquaculture, reduces production costs and carbon footprint, and promotes a circular economy. Brewer’s spent grain (BSG) is one such by-product. Solid-state fermentation (SSF) of BSG with Aspergillus ibericus enhances its nutritional value and digestibility for European seabass. The present study further evaluates the potential of dietary inclusion of BSG-SSF on growth performance, feed utilization, plasma metabolite profile, intermediary metabolism, and oxidative status of European seabass juveniles compared to the unfermented product. A practical diet (45% protein; 18% lipids) was tested against diets incorporating 10% or 20% of BSG or BSG-SSF, replacing plant-protein feedstuffs. Triplicate groups of European seabass juveniles (49 g initial weight) were fed for 10 weeks. Unfermented BSG (10% and 20%) reduced growth and feed efficiency. In comparison, the 20% BSG-SSF diet promoted growth and feed efficiency similar to the control group, while the 10% BSG-SSF diet surpassed the control diet. Whole-body protein content was unaffected, but lipid and energy content decreased with increasing BSG levels, regardless of fermentation. Plasma glucose and phospholipid levels and hepatic activities of glucokinase and malic enzymes decreased with increasing BSG, irrespective of fermentation. BSG-SSF incorporation increased plasma triglyceride levels and decreased hepatic transaminase activities but did not affect hepatic key enzyme activity of β-oxidation or lipogenesis. It also reduced antioxidant enzyme activity and lipid peroxidation. In conclusion, BSG negatively impacted growth performance, while BSG-SSF supported inclusion levels up to 20% without performance loss. Further, the 10% BSG -SSF diet outperformed the control diet.

Immunological mechanisms involved in the protection against development of pulmonary tuberculosis in naturally infected goats - Irene Agulló-Ros; Rita Vaz-Rodrigues; Mercedes Domínguez; Álvaro Roy; Javier Ortega; Inmaculada Moreno; Javier Bezos; Lucas Domínguez; Isabel G. Fernández de Mera; María A. Risalde (Veterinary Microbiology, 2025)

Feasibility of successive hydrogen and methane production: Effects of temperature and organic loads on energy potential and microbial dynamics - Kauanna Uyara Devens; Alexandre Rodrigues Ribeiro; Franciele Pereira Camargo; Isabel Kimiko Sakamoto; Maria Bernadete Amâncio Varesche; Edson Luiz Silva (International Biodeterioration & Biodegradation, 2025)

Modeling the protective effect of water activity of a meat emulsion matrix model on Listeria monocytogenes inactivation by high pressure processing - Natália Brunna Moresco Ferreira; Maria Isabel Rodrigues; Marcelo Cristianini (Food Control, 2025)

Correlation between ultrasound evaluation of the prostate and age, weight, kinetics and sperm morphology of German Spitz breeders - Bruno Alcantara Buzato; Luiz Guilherme Corsi Trautwein; Myrian Megumy Tsunokawa Hidalgo; Leticia Amanda dos Santos Silva; Julia Rodrigues Greghi; Vinicius Wagner Silva; Natalia Ribeiro Sambatti; Maria Isabel Mello Martins (Animal Reproduction Science, 2025)

Vibrational spectroscopic techniques and variable selection in Linear Discriminant Analysis to geographical origin discrimination of Jatropha mollissima sap - Caroline Lins Fernandes; Tiago Santos Silva; Caike Lobo Rodrigues de Lima; Isabel Cristina Vicente dos Santos; Djair Araújo Fialho; Marcus Vinicius Lia Fook; Paulo Henrique Gonçalves Dias Diniz; José Filipe Bacalhau Rodrigues; Simone da Silva Simões (Phytochemistry Letters, 2024)

Mesoproterozoic depleted spinel peridotites metasomatized by high-K hydrous melt in the Patagonian back-arc - Aline Alves dos Santos; Tiago Jalowitzki; Fernanda Gervasoni; Maurizio Mazzucchelli; Tommaso Giovanardi; Manuel Enrique Schilling; Maria Isabel Varas-Reus; Yuji Orihashi; Rodrigo Freitas Rodrigues; Richard Walter Carlson; Georgina Marianela Rubiano Lorenzoni; Daiji Hirata; et al. (Chemical Geology, 2024)

SUMOylation of rice DELLA SLR1 modulates transcriptional responses and improves yield under salt stress - Telma Fernandes; Nuno M. Gonçalves; Cleverson C. Matiolli; Mafalda A. A. Rodrigues; Pedro M. Barros; M. Margarida Oliveira; Isabel A. Abreu (Planta, 2024)
Main conclusion SUMOylation of SLR1 at K2 protects productivity under salt stress, possibly by modulation of SLR1 interactome. Abstract DELLA proteins modulate GA signaling and are major regulators of plant plasticity to endure stress. DELLAs are mostly regulated at the post-translational level, and their activity relies on the interaction with upstream regulators and transcription factors (TFs). SUMOylation is a post-translational modification (PTM) capable of changing protein interaction and has been found to influence DELLA activity in Arabidopsis. We determined that SUMOylation of the single rice DELLA, SLENDER RICE1 (SLR1), occurs in a lysine residue different from the one identified in Arabidopsis REPRESSOR OF GA (RGA). Artificially increasing the SUMOylated SLR1 levels attenuated the penalty of salt stress on rice yield. Gene expression analysis revealed that the overexpression of SUMOylated SLR1 can regulate GA biosynthesis, which could partially explain the sustained productivity upon salt stress imposition. Furthermore, SLR1 SUMOylation blocked the interaction with the growth regulator YAB4, which may fine-tune GA20ox2 expression. We also identified novel SLR1 interactors: bZIP23, bHLH089, bHLH094, and OSH1. All those interactions were impaired in the presence of SUMOylated SLR1. Mechanistically, we propose that SUMOylation of SLR1 disrupts its interaction with several transcription factors implicated in GA-dependent growth and ABA-dependent salinity tolerance to modulate downstream gene expression. We found that SLR1 SUMOylation represents a novel mechanism modulating DELLA activity, which attenuates the impact of stress on plant performance.

Correction: Performance assessment of a new serological diagnostic test for COVID-19 with candidate peptides from spike and nucleocapsid viral proteins - Vanessa de Melo Cavalcanti-Dantas; Alan Frazão da Silva; Andrei Félix Mendes; Waldecir Oliveira de Araújo Júnior; Lucas Coêlho Bernardo-Menezes; Cristiane Campello Bresani-Salvi; Lúcio Roberto Cançado Castellano; Ana Isabel Vieira Fernandes; Sherlan Guimarães Lemos; Jurandy Júnior Ferraz de Magalhães; Renato Antônio dos Santos Oliveira; Priscilla Anne Castro de Assis; et al. (Brazilian Journal of Microbiology, 2024)

Plastisphere in a low-pollution mountain river: Influence of microplastics on survival of pathogenic bacteria - Isabel Silva; Elsa T. Rodrigues; Marta Tacão; Isabel Henriques (Chemosphere, 2024)

Isolation and identification of native Chilean entomopathogenic fungi and their potential for the control of Drosophila suzukii - Cristian Montalva; Cristian González; Cecilia Ruiz; Isabel Vives; Andrea Díaz; Luis Devotto; Juscelino Rodrigues; Luiz F.N. Rocha; Javiera Manríquez; Tania Vásquez; Richard A. Humber; Christian Luz (Journal of Invertebrate Pathology, 2024)

Influence of paternal factors on plastic ingestion and brominated chemical exposure in East Tropical Atlantic Procellariid chicks - Diana M. Matos; J.A. Ramos; A.L.C. Brandão; Francisca Baptista; Isabel Rodrigues; J.O. Fernandes; L.A.E. Batista de Carvalho; M.P.M. Marques; S.C. Cunha; Stefan Antunes; V.H. Paiva (Science of The Total Environment, 2024)

Novel cold and thermally pasteurized cardoon-enriched functional smoothie formulations: A zero-waste manufacturing approach - Filipa Mandim; Spyridon A. Petropoulos; Carlos A. Pinto; Sandrina A. Heleno; Paula Rodrigues; Maria Inês Dias; Jorge A. Saraiva; Celestino Santos-Buelga; Isabel C.F.R. Ferreira; Lillian Barros; José Pinela (Food Chemistry, 2024)

Effect of solid-state fermentation of Brewer's spent grain on digestibility and digestive function of european seabass (Dicentrarchus labrax) juveniles - Tássia Estevão-Rodrigues; Helena Fernandes; Sara Moutinho; Diogo Filipe; Filipa Fontinha; Rui Magalhães; Ana Couto; Marta Ferreira; Margarida Gamboa; Carolina Castro; Isabel Belo; José Salgado; et al. (Animal Feed Science and Technology, 2024)

Assessing interpreter’s disagreements in land cover reference data collection from historical Landsat time series in Amazon - Mariane S. Reis; Lucélia S. de Barros; Manoel R. Rodrigues Neto; Dayane Rafaela V. de Moraes; Noeli Aline P. Moreira; Gabriel Mikael R. Alves; Bruno V. Adorno; Cassiano Gustavo Messias; Luciano V. Dutra; Camilo D. Rennó; Sidnei João S. Sant’Anna; Maria Isabel S. Escada (International Journal of Remote Sensing, 2024)

Ten years of directing seeding restoration in the Brazilian savanna: Lessons learned and the way forward - Ana Wiederhecker; Maxmiller Cardoso Ferreira; Silvia Barbosa Rodrigues; Alexandre Bonesso Sampaio; Isabel Belloni Schmidt; José Felipe Ribeiro; Roberto Shojirou Ogata; Maísa Isabela Rodrigues; Augusto Cesar Silva-Coelho; Icaro Sousa Abreu; Thaís Franco Montenegro; Daniel Luis Mascia Vieira (Journal of Environmental Management, 2024)

Type III sourdough: Evaluation of biopreservative potential in bakery products with enhanced antifungal activity - Lílian Borges Teixeira; Júlia Zanini Campos; Caroline Isabel Kothe; Juliane Elisa Welke; Eliseu Rodrigues; Jeverson Frazzon; Roberta Cruz Silveira Thys (Food Research International, 2024)

Performance assessment of a new serological diagnostic test for COVID-19 with candidate peptides from spike and nucleocapsid viral proteins - Vanessa de Melo Cavalcanti-Dantas; Alan Frazão da Silva; Andrei Félix Mendes; Waldecir Oliveira de Araújo Júnior; Lucas Coêlho Bernardo-Menezes; Cristiane Campello Bresani-Salvi; Lúcio Roberto Cançado Castellano; Ana Isabel Vieira Fernandes; Sherlan Guimarães Lemos; Jurandy Júnior Ferraz de Magalhães; Renato Antônio dos Santos Oliveira; Priscilla Anne Castro de Assis; et al. (Brazilian Journal of Microbiology, 2024)

Cetaceans of north-western continental Africa (Morocco to Liberia): diversity and distribution - Ana M. Correia; Marieta Mihova; Ágatha Gil; Cláudia Oliveira-Rodrigues; Luís Afonso; Raul Valente; Massimiliano Rosso; Isabel Sousa-Pinto; Graham J. Pierce (Frontiers in Marine Science, 2024)
The north-western coast of Africa is one of the most productive marine systems in the world, where a high diversity of cetacean species has been recorded. However, management of human activities that impact cetacean populations in the area is inadequate, in part due to poor knowledge on cetacean occurrence and the lack of systematic surveys. We reviewed existing knowledge on cetacean distribution between Morocco and Liberia and analyzed the spatial and temporal distribution of records, as well as species occurrence, further discussing the reported distribution ranges. The systematic literature review included 39 sources reporting on 36 species in the area, with a total of 2241 sightings and 2178 non-sighting records. Delphinus delphis (common dolphin) and Tursiops truncatus (bottlenose dolphin) are the two species with the highest number of sources reporting on them. This review reveals a spatially and temporally heterogeneous coverage of the area in the literature and published data on cetacean occurrence. In summary, although most of the compiled sources are recently published (2011-2020), the majority of records are from prior to 2000. In several range states, especially south of Senegal, little information is available. Therefore, the available information is unlikely to represent the current status of cetacean communities in the region. It is essential to fill knowledge gaps by increasing the collection of cetacean distribution data in the area, in order to support effective conservation measures and ensure sustainable utilization of the living marine resources in this rapidly developing region.

Wild animal trafficking in Brazil: challenges for fauna protection - Bárbara Figueiredo Ambrogi; Antonio Rodrigues da Cunha Neto; Marielle Rezende de Andrade; Wilson Vicente Souza Pereira; Isabel Ribeiro do Valle Teixeira (Environment, Development and Sustainability, 2024)

Integron-associated genes are reliable indicators of antibiotic resistance in wastewater despite treatment- and seasonality-driven fluctuations - Rafael D.S. Tavares; Cátia Fidalgo; Elsa T. Rodrigues; Marta Tacão; Isabel Henriques (Water Research, 2024)

Towards a circular bioeconomy to produce methane by co-digestion of coffee and brewery waste using a mixture of anaerobic granular sludge and cattle manure as inoculum - Caroline Varella Rodrigues; Franciele Pereira Camargo; Vitor Alves Lourenço; Isabel Kimiko Sakamoto; Sandra Imaculada Maintinguer; Edson Luiz Silva; Maria Bernadete Amâncio Varesche (Chemosphere, 2024)

Unlocking potential: Exploring the methane production potential in anaerobic co-digestion of cassava wastewater and glycerol - Kauanna Uyara Devens; Alexandre Rodrigues Ribeiro; Franciele Pereira Camargo; Isabel Kimiko Sakamoto; Maria Bernadete Amâncio Varesche; Edson Luiz Silva (Journal of Environmental Chemical Engineering, 2024)

The putative cannabinoid-secreting trichome of Trema micrantha (L.) Blume (Cannabaceae) - Simone Pádua Teixeira; Isabel Cristina Nascimento; Marina Priolo Grejo; Viviane Gonçalves Leite; Sílvia Rodrigues Machado (Protoplasma, 2024)

Camera trap surveys of A tlantic F orest mammals: A data set for analyses considering imperfect detection (2004–2020) - Ingridi Camboim Franceschi; Rubem Augusto da Paixão Dornas; Isabel Salgueiro Lermen; Artur Vicente Pfeifer Coelho; Ademir Henrique Vilas Boas; Adriano Garcia Chiarello; Adriano Pereira Paglia; Agnis Cristiane de Souza; Alana Rafaela Borsekowsky; Alessandro Rocha; Alex Bager; Alexander Zaidan de Souza; et al. (Ecology, 2024)
Camera traps became the main observational method of a myriad of species over large areas. Data sets from camera traps can be used to describe the patterns and monitor the occupancy, abundance, and richness of wildlife, essential information for conservation in times of rapid climate and land‐cover changes. Habitat loss and poaching are responsible for historical population losses of mammals in the Atlantic Forest biodiversity hotspot, especially for medium to large‐sized species. Here we present a data set from camera trap surveys of medium to large‐sized native mammals (>1 kg) across the Atlantic Forest. We compiled data from 5380 ground‐level camera trap deployments in 3046 locations, from 2004 to 2020, resulting in 43,068 records of 58 species. These data add to existing data sets of mammals in the Atlantic Forest by including dates of camera operation needed for analyses dealing with imperfect detection. We also included, when available, information on important predictors of detection, namely the camera brand and model, use of bait, and obstruction of camera viewshed that can be measured from example pictures at each camera location. Besides its application in studies on the patterns and mechanisms behind occupancy, relative abundance, richness, and detection, the data set presented here can be used to study species' daily activity patterns, activity levels, and spatiotemporal interactions between species. Moreover, data can be used combined with other data sources in the multiple and expanding uses of integrated population modeling. An R script is available to view summaries of the data set. We expect that this data set will be used to advance the knowledge of mammal assemblages and to inform evidence‐based solutions for the conservation of the Atlantic Forest. The data are not copyright restricted; please cite this paper when using the data.

Responses of soil microbiome to copper-based materials (nano and bulk) for agricultural applications: An indoor-mesocosm experiment - Sara Peixoto; Rui G. Morgado; Marija Prodana; Diogo N. Cardoso; Catarina Malheiro; Joana Neves; Cátia Santos; Zahra Khodaparast; Maria D. Pavlaki; Sandra Rodrigues; Sónia M. Rodrigues; Isabel Henriques; et al. (NanoImpact, 2024)

Immunomodulatory effect of Lacticaseibacillus casei CB054 supplementation in calves vaccinated against infectious bovine rhinotracheitis - Carolina Litchina Brasil; Vitória Sequeira Gonçalves; Francisco Denis Souza Santos; Paulo Ricardo Centeno Rodrigues; Fábio Pereira Leivas Leite; Daniela Isabel Brayer Pereira (Veterinary Immunology and Immunopathology, 2024)

Sustainable rice bran protein: Composition, extraction, quality properties and applications - Silvia Leticia Rivero Meza; Lázaro Cañizares; Brenda Dannenberg; Betina Bueno Peres; Larissa Alves Rodrigues; Celina Mardade; Maria Antônia de Leon; César Augusto Gaioso; Isabel Egea; Mauricio de Oliveira (Trends in Food Science & Technology, 2024)

Microplastics ingestion and endocrine disrupting chemicals (EDCs) by breeding seabirds in the east tropical Atlantic: Associations with trophic and foraging proxies (δ15N and δ13C) - Diana M. Matos; J.A. Ramos; A.L.C. Brandão; Alexandra Baeta; Isabel Rodrigues; I. dos Santos; João Coentro; J.O. Fernandes; L.A.E. Batista de Carvalho; M.P.M. Marques; S.C. Cunha; S.H. Santos; et al. (Science of The Total Environment, 2024)

A streamflow regionalization method using hydrological data and geoprocessing tools—a Brazilian midwest analysis - Luiz Felipe Finck; Izabel Rodrigues Leite; Aleska Kaufmann Almeida; Isabel Kaufmann de Almeida (Journal of South American Earth Sciences, 2024)

Reproductive seasonality of hair rams under tropical conditions: an alternative for non-seasonal lamb production? - Arnaldo de Sá Geraldo; Pedro Henrique Nicolau Pinto; Ana Beatriz da Silva Carvalho; Marta Maria Campos Pereira da Costa; Juliana Dantas Rodrigues Santos; Augusto Ryonosuke Taira; Isabel Oliveira Cosentino; Bruna Ramalho Rigaud de Figueiredo; Mário Felipe Alvarez Balaro; Rodolfo Ungerfeld; Felipe Zandonadi Brandão (Tropical Animal Health and Production, 2024)

Optimized conditions for methane production and energy valorization through co-digestion of solid and liquid wastes from coffee and beer industries using granular sludge and cattle manure - Caroline Varella Rodrigues; Franciele Pereira Camargo; Vitor Alves Lourenço; Isabel Kimiko Sakamoto; Sandra Imaculada Maintinguer; Edson Luiz Silva; Maria Bernadete Amâncio Varesche (Journal of Environmental Chemical Engineering, 2023)

An improved reference genome and first organelle genomes of Quercus suber - Ana Usié; Octávio Serra; Pedro M. Barros; Pedro Barbosa; Célia Leão; Tiago Capote; Tânia Almeida; Leandra Rodrigues; Isabel Carrasquinho; Joana B. Guimarães; Diogo Mendoça; Filomena Nóbrega; et al. (Tree Genetics & Genomes, 2023)
Cork oak ( Quercus suber L.) is an ecologically and economically important evergreen tree species native to the Mediterranean region and widespread in southwest Europe and northwest Africa. An improved genome assembly of cork oak using a combination of Illumina and PacBio sequencing is presented in this study. The assembled genome contains 2351 scaffolds longer than 1000 bp, accounting for 765.7 Mbp of genome size, L90 of 755, and a N50 of 1.0 Mbp, with 40,131 annotated genes. The repetitive sequences constitute 53.6% of the genome. The genome sequences of chloroplast and mitochondrion were determined for the first time, with a genome size of 161,179 bp and 531,858 bp, respectively. Phylogenetic analysis based on complete chloroplast genome sequence showed that Q. suber is closely related to Quercus variabilis , two cork-producing species with commercial use. All data generated are available through the public databases, being ready to be used without restrictions. This study provides an improved nuclear genome assembly together with the organelle genomes of cork oak. These resources will be useful for further breeding strategies and conservation programs and for comparative genomic studies in oak species.

Emergency cesarean section in dogs: Usefulness of amniotic fluid biochemical parameters and placental morphology as indicators of neonatal viability - Julia Rodrigues Greghi; Phelipe Oliveira Favaron; Luiz Guilherme Corsi Trautwein; Caio Garcia Barbosa da Silva; Gisele Augusta Amorim de Lemos; Maria Isabel Mello Martins (Theriogenology, 2023)

Anthropogenic debris ingestion in a tropical seabird community: Insights from taxonomy and foraging distribution - D.M. Matos; J.A. Ramos; Filipa Bessa; Vítor Silva; Isabel Rodrigues; Stefan Antunes; I. dos Santos; João Coentro; A.L.C. Brandão; L.A.E. Batista de Carvalho; M.P.M. Marques; Sara Santos; et al. (Science of The Total Environment, 2023)

Microencapsulation of Limosilactobacillus reuteri (DSM 23878) for application in infant formula: Heat resistance and bacterial viability during long-time storage - Mariana Alves Gragnani Vido; Izabela Dutra Alvim; Gabriel Vinderola; Maria Isabel Berto; Patricia Blumer Zacarchenco Rodrigues de Sá; Cristian Mauricio Barreto Pinilla; Adriana Torres Silva e Alves (Food Research International, 2023)

First record of a live adult heteropod Firoloida desmarestia in the Red Sea - Carlos Angulo-Preckler; Alexandra Steckbauer; Isabel Armelles; Susana Agustí; Mattie Rodrigue; Vincent Pieribone; Mohammad Qurban; Carlos M. Duarte (Frontiers in Marine Science, 2023)
Observations are essential to explore and discover the ocean. The rapid advancements in technology have revolutionized our capacity to document the ocean and its diverse array of species, pushing the boundaries of our understanding further than ever before. The central Red Sea was exposed as part of the Red Sea Decade Expedition , which took place from 04 February to 18 June 2022 aboard the R/V OceanXplorer, using underwater submersibles. Here, for the first time in the Red Sea, we reported three observations of living Firoloida desmarestia specimens, one female and two male specimens, a heteropod from the Pterotracheidae family. This shell-less mollusk has been observed in the epipelagic zone of the world’s oceans, with the exception of polar regions, suggesting a global distribution for these observations. The two males were observed swimming in the water column, while the female was close to the seabed. All three observations were detected during the morning, raising the question if these organisms use vertical migrations to reach deep-sea waters during the daytime. However, no ROV or submersible dives were conducted at night. Our results show a depth range expansion for observations of this species in the Red Sea. Furthermore, as far as we know, no adults of F. desmarestia have been reported until now in the Red Sea. During the expedition, all three specimens were found at similar depths (350, 400, and 464.5 m depth), with the female being the deepest, thus confirming the eurybathic distribution of this species. The emerging technology is progressively enhancing our understanding of these enigmatic creatures and expanding our knowledge of their fascinating adaptations and ecological roles. In addition to our fieldwork, a literature search was performed to uncover any pre-existing observational records of this species to understand its global distribution and ecological significance.

Effect of high pressure processing and water activity on pressure resistant spoilage lactic acid bacteria (Latilactobacillus sakei) in a ready-to-eat meat emulsion model - Natália Brunna Moresco Ferreira; Maria Isabel Rodrigues; Marcelo Cristianini (International Journal of Food Microbiology, 2023)

Microplastics accumulate priority antibiotic-resistant pathogens: Evidence from the riverine plastisphere - Isabel Silva; Elsa T. Rodrigues; Marta Tacão; Isabel Henriques (Environmental Pollution, 2023)

The potential of almonds, hazelnuts, and walnuts SFE-CO2 extracts as sources of bread flavouring ingredients - Júlia C. Kessler; Vanessa Vieira; Isabel M. Martins; Yaidelin A. Manrique; Patrícia Ferreira; Ricardo C. Calhelha; Andreia Afonso; Lillian Barros; Alírio E. Rodrigues; Madalena M. Dias (Food Chemistry, 2023)

First report of phenolic compounds isolated from Inga stipularis DC. (fabaceae) leaves - Anderson de Santana Botelho; Wandson Braamcamp de Souza Pinheiro; José Rodrigues Pinheiro Neto; Sonia das Graças Santa Rosa Pamplona; Kyouk Isabel Portilho dos Santos; Milton Nascimento da Silva; Mara Silvia Pinheiro Arruda (Natural Product Research, 2023)

Use of MIR spectroscopy associated with chemometric techniques to verify the authenticity of prato cheese - Isabel Cristina de Santana Alves Tolentino; Josane Cardim de Jesus; Daniele Gomes Conceição; Rebeca Rodrigues Vieira Onelli; Lucas Caiafa Cardoso Reis; Leandro Soares Santos; Sibelli Passini Barbosa Ferrão (International Dairy Journal, 2023)

DNA metabarcoding to assess prey overlap between tuna and seabirds in the Eastern tropical Atlantic: Implications for an ecosystem-based management - Ana Rita Carreiro; Jaime A. Ramos; Vanessa A. Mata; Nathalie M. Almeida; Isabel Rodrigues; Ivo dos Santos; Diana M. Matos; Pedro M. Araújo; Teresa Militão; Jacob González-Sólis; Vitor H. Paiva; Ricardo Jorge Lopes (Marine Environmental Research, 2023)

Impact of climate changes in the suitable areas for Coffea arabica L. production in Mozambique: Agroforestry as an alternative management system to strengthen crop sustainability - Crimildo T. Cassamo; David Draper; Maria M. Romeiras; Isabel Marques; Rogério Chiulele; Marisa Rodrigues; Marc Stalmans; Fábio L. Partelli; Ana Ribeiro-Barros; José C. Ramalho (Agriculture, Ecosystems & Environment, 2023)

Biomethane recovery through co-digestion of cheese whey and glycerol in a two-stage anaerobic fluidized bed reactor: Effect of temperature and organic loading rate on methanogenesis - Priscilla de Souza Almeida; Camila Aparecida de Menezes; Franciele Pereira Camargo; Isabel Kimiko Sakamoto; Giovanna Lovato; José Alberto Domingues Rodrigues; Maria Bernadete Amâncio Varesche; Edson Luiz Silva (Journal of Environmental Management, 2023)

Atlantic flower–invertebrate interactions: A data set of occurrence and frequency of floral visits - Danilo Boscolo; Bárbara Nobrega Rodrigues; Patrícia Alves Ferreira; Luciano Elsinor Lopes; Vinicius Rodrigues Tonetti; Isabela Cristhina Reis dos Santos; Juliana Akemi Hiruma‐Lima; Laura Nery; Karoline Baptista de Lima; Jéssica Perozi; André Victor Lucci Freitas; Blandina Felipe Viana; et al. (Ecology, 2023)
Encounters between flowers and invertebrates are key events for the functioning of tropical forests. Assessing the structure of networks composed of the interactions between those partners leads to a better understanding of ecosystem functioning and the effects of environmental factors on ecological processes. Gathering such data is, however, costly and time‐consuming, especially in the highly diverse tropics. We aimed to provide a comprehensive repository of available flower–invertebrate interaction information for the Atlantic Forest, a South American tropical forest domain. Data were obtained from published works and “gray literature,” such as theses and dissertations, as well as self‐reports by co‐authors. The data set has ~18,000 interaction records forming 482 networks, each containing between one and 1061 interaction links. Each network was sampled for about 200 h or less, with few exceptions. A total of 641 plant genera within 136 different families and 39 orders were reported, with the most abundant and rich families being Asteraceae, Fabaceae, and Rubiaceae. Invertebrates interacting with these plants were all arthropods from 10 orders, 129 families, and 581 genera, comprising 2419 morphotypes (including 988 named species). Hymenoptera was the most abundant and diverse order, with at least six times more records than the second‐ranked order (Lepidoptera). The complete data set shows Hymenoptera interacting with all plant orders and also shows Diptera, Lepidoptera, Coleoptera, and Hemiptera to be important nodes. Among plants, Asterales and Fabales had the highest number of interactions. The best sampled environment was forest (~8000 records), followed by pastures and crops. Savanna, grasslands, and urban environments (among others) were also reported, indicating a wide range of approaches dedicated to collecting flower–invertebrate interaction data in the Atlantic Forest domain. Nevertheless, most reported data were from forest understory or lower strata, indicating a knowledge gap about flower–invertebrate interactions at the canopy. Also, access to remote regions remains a limitation, generating sampling bias across the geographical range of the Atlantic Forest. Future studies in these continuous and hard‐to‐access forested areas will yield important new information regarding the interactions between flowers and invertebrates in the Atlantic Forest. There are no copyright restrictions on the data set. Please cite this data paper if the data are used in publications and teaching events.

Rare earth elements as statistical sentinels of pollution and paleoenvironments?: Application to a highly polluted estuary in southwestern Spain - Verónica Romero; Francisco Ruiz; María Isabel Prudencio; Juan Manuel Muñoz; Joaquín Rodríguez Vidal; Paula Gómez; Manuel Abad; Tatiana Izquierdo; María Isabel Dias; Rosa Marques; Ana Luisa Rodrigues; Luis Miguel Cáceres; et al. (Marine Pollution Bulletin, 2023)

Improving the accuracy of beef cattle methane inventories in Latin America and Caribbean countries - Guilhermo F.S. Congio; André Bannink; Olga L. Mayorga; João P.P. Rodrigues; Adeline Bougouin; Ermias Kebreab; Paulo C.F. Carvalho; Telma T. Berchielli; Maria E.Z. Mercadante; Sebastião C. Valadares-Filho; Ana L.C.C. Borges; Alexandre Berndt; et al. (Science of The Total Environment, 2023)

Granulated biomass fly ash coupled with fenton process for pulp and paper wastewater treatment - João Peres Ribeiro; Nuno C. Cruz; Márcia C. Neves; Sónia M. Rodrigues; Luís A.C. Tarelho; Maria Isabel Nunes (Environmental Pollution, 2023)

Rock n' Seeds: A database of seed functional traits and germination experiments from Brazilian rock outcrop vegetation - Carlos A. Ordóñez‐Parra; Roberta L. C. Dayrell; Daniel Negreiros; Antônio C. S. Andrade; Letícia G. Andrade; Yasmine Antonini; Leilane C. Barreto; Fernanda de V. Barros; Vanessa da Cruz Carvalho; Blanca Auxiliadora Dugarte Corredor; Antônio Cláudio Davide; Alexandre A. Duarte; et al. (Ecology, 2023)
Advancing functional ecology depends fundamentally on the availability of data on reproductive traits, including those from tropical plants, which have been historically underrepresented in global trait databases. Although some valuable databases have been created recently, they are mainly restricted to temperate areas and vegetative traits such as leaf and wood traits. Here, we present Rock n' Seeds, a database of seed functional traits and germination experiments from Brazilian rock outcrop vegetation, recognized as outstanding centers of diversity and endemism. Data were compiled through a systematic literature search, resulting in 103 publications from which seed functional traits were extracted. The database includes information on 16 functional traits for 383 taxa from 148 genera, 50 families, and 25 orders. These 16 traits include two dispersal, six production, four morphological, two biophysical, and two germination traits—the major axes of the seed ecological spectrum. The database also provides raw data for 48 germination experiments, for a total of 10,187 records for 281 taxa. Germination experiments in the database assessed the effect of a wide range of abiotic and biotic factors on germination and different dormancy‐breaking treatments. Notably, 8255 of these records include daily germination counts. This input will facilitate synthesizing germination data and using this database for a myriad of ecological questions. Given the variety of seed traits and the extensive germination information made available by this database, we expect it to be a valuable resource advancing comparative functional ecology and guiding seed‐based restoration and biodiversity conservation in tropical megadiverse ecosystems. There are no copyright restrictions on the data; please cite this paper when using the current data in publications; also the authors would appreciate notification of how the data are used in publications.

Sexual segregation in the foraging distribution, behaviour, and trophic niche of the endemic Boyd’s shearwater (Puffinus lherminieri boydi) - Ivo dos Santos; Jaime A. Ramos; Filipe R. Ceia; Isabel Rodrigues; Nathalie Almeida; Stefan Antunes; Ana R. Carreiro; Diana M. Matos; Ricardo J. Lopes; Pedro Geraldes; Vítor H. Paiva (Marine Biology, 2022)

In vitro sensitivity of Xanthomonas vasicola pv. vasculorum and the control of bacterial leaf streak of corn with copper oxychloride alone and in mixtures with mancozeb and fluxapyroxad - Izabela Moura Duin; Thayná Aparecida Forasteiro; Vanessa Hitomi Sugahara Rodrigues; Maria Isabel Balbi-Peña; Rui Pereira Leite Júnior (European Journal of Plant Pathology, 2022)

Seasonal approach to forecast the suitability of spawning habitats of a temperate small pelagic fish under a high-emission climate change scenario - André R. A. Lima; Susana Garrido; Isabel Riveiro; Diana Rodrigues; Maria M. P. Angélico; Emanuel J. Gonçalves; Myron A. Peck; Gonçalo Silva (Frontiers in Marine Science, 2022)
Spawning habitats of cold-water, European small pelagic fishes have shifted poleward in the last three decades coincident with gradual ocean warming. We predicted present-day, season-specific habitat suitability for spawning by European sardine Sardina pichardus in the Atlantic Ocean and Mediterranean and Black Seas, and projected climate-driven changes in suitable areas from 2050-2099 under the IPCC – RCP 8.5 scenario. Sea surface temperature and distance to the coast had the greater influences in spawning habitats, reflecting the temperature- and coastal-dependent spawning of sardines. Chlorophyll- a was the third most important explanatory variable for spawning in winter to summer. Winds were predominantly important during autumn, whilst sea surface salinity was an important driver during spring and summer. Present-day, “hotspots” for spawning were identified in regions of highly productive, salty waters, where SST was between 6 and 18°C from autumn to spring or 16 and 25°C during summer and favourable winds occurred that would retain eggs and larvae closer to the coast (< 250 km). For future scenarios, forecasts indicate that environmental optima for spawning is projected to be in regions where SST varies between 11°C and 18°C from autumn to spring; and between 18°C and 24°C during summer. However, a negative relationship between phytoplankton productivity and habitat suitability induced by warming is likely to occur in the future. Projections suggest that suitable spawning habitats in all seasons will shift to higher latitudes, with a prominent range expansion along the coast of Norway during winter and autumn (> 83%). The total spawning area, however, was projected to contract in the future during spring (-10.5%) and autumn (-4.1%) due to losses of currently suitable areas along the Atlantic African Coast and Mediterranean Sea. Such regions currently support the greatest sardine stocks but climate-driven warming and decreased plankton productivity are projected to make these areas unsuitable for spawning and likely also for sardine fisheries in future.

Ambient vibration testing and seismic fragility analysis of masonry building aggregates - Vasco Miguel Serrano Bernardo; Alfredo Peres de Noronha Campos Costa; Paulo José de Oliveira Xavier Candeias; Aníbal Guimarães da Costa; Ana Isabel Mera Marques; Alexandra Rodrigues Carvalho (Bulletin of Earthquake Engineering, 2022)

Involvement of serotonergic neurotransmission in the antidepressant-like effect elicited by cholecalciferol in the chronic unpredictable stress model in mice - Vivian B. Neis; Isabel Werle; Morgana Moretti; Priscila B. Rosa; Anderson Camargo; Yasmim de O. Dalsenter; Nicolle Platt; Axel F. Rosado; William D. Engel; Gudrian Ricardo L. de Almeida; Ingrid Selhorst; Alcir Luiz Dafre; et al. (Metabolic Brain Disease, 2022)

Foraging costs drive within-colony spatial segregation in shearwaters from two contrasting environments in the North Atlantic Ocean - Jorge M. Pereira; Jaime A. Ramos; Nathalie Almeida; Pedro M. Araújo; Filipe R. Ceia; Pedro Geraldes; Ana M. Marques; Diana M. Matos; Isabel Rodrigues; Ivo dos Santos; Vitor H. Paiva (Oecologia, 2022)

Non-material nature’s contributions to people from a marine protected area support multiple dimensions of human well-being - João Garcia Rodrigues; Sebastián Villasante; Isabel Sousa Pinto (Sustainability Science, 2022)
The non-material aspects of nature are frequently the most socially valued and demanded nature’s contributions to people (NCP). This is because non-material NCP often lay the foundations of key human well-being dimensions such as identities, experiences, and capabilities. Yet, while research on material NCP such as food and water abound, studies of non-material NCP are relatively scarce. This research gap results in a limited understanding of the relationships between non-material NCP and human well-being, especially in the marine and coastal environment. To understand the relationships between non-material NCP and subjective human well-being, we surveyed 453 users of Litoral Norte—a multiple-use marine protected area in Portugal. Our survey included 16 statement indicators reflecting theoretical constructs of subjective well-being. Using factor analysis, we found that subjective well-being derived from relating to, interacting with, and experiencing marine and coastal sites can be grouped into four interpretable cultural dimensions of well-being. These dimensions are ‘engagement with nature & health’, ‘sense of place’, ‘solitude in nature’, and ‘spirituality’. We also found statistically significant differences in reported levels of the four dimensions of well-being. Reported levels of well-being varied with interviewees’ socio-economic characteristics and environmental behaviour. Our findings offer interesting insights for marine conservation practice and policy that aims to foster both biodiversity and human well-being.

Indigenous and local communities can boost seed supply in the UN decade on ecosystem restoration - Danilo Urzedo; Simone Pedrini; Daniel L. M. Vieira; Alexandre B. Sampaio; Bruna D. F. Souza; Eduardo Malta Campos-Filho; Fatima C. M. Piña-Rodrigues; Isabel B. Schmidt; Rodrigo G. P. Junqueira; Kingsley Dixon (Ambio, 2022)
The UN Decade of Ecosystem Restoration is poised to trigger the recovery of ecosystem services and transform structural injustices across the world in a way unparalleled in human history. The inclusion of diverse Indigenous and local communities to co-create robust native seed supply systems is the backbone to achieve the goals for the Decade. Here we show how community-based organizations have co-developed native seed supply strategies for landscape restoration from the bottom-up. We draw on the interconnections over two decades of seed networks in Brazil and the emerging Indigenous participation in native seed production in Australia. From an environmental justice perspective, we provide a participatory seed supply approach for local engagement, noting local geographical, social and cultural contexts. Meeting large-scale restoration goals requires the connection between local seed production and collaborative platforms to negotiate roles, rights and responsibilities between stakeholders. An enduring native seed supply must include a diversity of voices and autonomy of community groups that builds equitable participation in social, economic, and environmental benefits.

ATLANTIC POLLINATION: a data set of flowers and interaction with nectar‐feeding vertebrates from the Atlantic Forest - Joice Iamara‐Nogueira; Natália Targhetta; Gina Allain; Adriano Gambarini; Alessandra R. Pinto; Ana Maria Rui; Andréa C. Araújo; Ariadna Lopes; Brenda Pereira‐Silva; Bruna Bertagni de Camargo; Caio Graco Machado; Caio Missagia; et al. (Ecology, 2022)
Flowering plant species and their nectar‐feeding vertebrates exemplify some of the most remarkable biotic interactions in the Neotropics. In the Brazilian Atlantic Forest, several species of birds (especially hummingbirds), bats, and non‐flying mammals, as well as one lizard feed on nectar, often act as pollinators and contribute to seed output of flowering plants. We present a dataset containing information on flowering plants visited by nectar‐feeding vertebrates and sampled at 166 localities in the Brazilian Atlantic Forest. This dataset provides information on 1902 unique interactions among 515 species of flowering plants and 129 species of potential vertebrate pollinators and the patterns of species diversity across latitudes. All plant–vertebrate interactions compiled were recorded through direct observations of visits, and no inferences of pollinators based on floral syndromes were included. We also provide information on the most common plant traits used to understand the interactions between flowers and nectar‐feeding vertebrates: plant growth form, corolla length, rate of nectar production per hour in bagged flowers, nectar concentration, flower color and shape, time of anthesis, presence or absence of perceptible fragrance by human, and flowering phenology as well as the plant’s threat status by International Union for Conservation of Nature (IUCN) classification. For the vertebrates, status of threat by IUCN classification, body mass, bill or rostrum size are provided. Information on the frequency of visits and pollen deposition on the vertebrate’s body is provided from the original source when available. The highest number of unique interactions is recorded for birds (1771) followed by bats (110). For plants, Bromeliaceae contains the highest number of unique interactions (606), followed by Fabaceae (242) and Gesneriaceae (104). It is evident that there was geographical bias of the studies throughout the southeast of the Brazilian Atlantic Forest and that most effort was directed to flower–hummingbird interactions. However, it reflects a worldwide tendency of more plants interacting with birds compared with other vertebrate species. The lack of similar protocols among studies to collect basic data limits the comparisons among areas and generalizations. Nevertheless, this dataset represents a notable effort to organize and highlight the importance of vertebrate pollinators in this hotspot of biodiversity on Earth and represents the data currently available. No copyright or proprietary restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications or scientific events.

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

Retina and Brain Display Early and Differential Molecular and Cellular Changes in the 3xTg-AD Mouse Model of Alzheimer’s Disease - Ana Catarina Rodrigues-Neves; Rafael Carecho; Sónia Catarina Correia; Cristina Carvalho; Elisa Julião Campos; Filipa Isabel Baptista; Paula Isabel Moreira; António Francisco Ambrósio (Molecular Neurobiology, 2021)

Antidepressant-like effect of guanosine involves activation of AMPA receptor and BDNF/TrkB signaling - Priscila B. Rosa; Luis E. B. Bettio; Vivian B. Neis; Morgana Moretti; Fernanda N. Kaufmann; Mauren K. Tavares; Isabel Werle; Yasmim Dalsenter; Nicolle Platt; Axel F. Rosado; Daiane B. Fraga; Isabella A. Heinrich; et al. (Purinergic Signalling, 2021)

Estimate the effects of environmental determining factors on childhood asthma hospital admissions in Lisbon, Portugal: a time series modelling study - Mónica Rodrigues; Isabel Natário; Maria do Rosário de Oliveira Martins (Theoretical and Applied Climatology, 2021)

Choosing an appropriate water quality model—a review - Cássia Monteiro da Silva Burigato Costa; Izabel Rodrigues Leite; Aleska Kaufmann Almeida; Isabel Kaufmann de Almeida (Environmental Monitoring and Assessment, 2021)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Producing electrical energy in microbial fuel cells based on sulphate reduction: a review - Isabel Cristina Braga Rodrigues; Versiane A. Leão (Environmental Science and Pollution Research, 2020)

Effect of Biochar on Emission of Greenhouse Gases and Productivity of Cardoon Crop (Cynara cardunculus L.) - Paulo Barracosa; Isabel Cardoso; Francisco Marques; António Pinto; Jorge Oliveira; Henrique Trindade; Pedro Rodrigues; José L. S. Pereira (Journal of Soil Science and Plant Nutrition, 2020)

Molecular epidemiology of invasive Haemophilus influenzae disease in Portugal: an update of the post-vaccine period, 2011–2018 - Catarina Isabel Moreira Heliodoro; Célia Rodrigues Bettencourt; Maria Paula Bajanca-Lavado (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Correction to: Ecological restoration as a strategy for mitigating and adapting to climate change: lessons and challenges from Brazil - Mercedes M. C. Bustamante; José Salomão Silva; Aldicir Scariot; Alexandre Bonesso Sampaio; Daniel Luis Mascia Vieira; Edenise Garcia; Edson Sano; Geraldo Wilson Fernandes; Giselda Durigan; Iris Roitman; Isabel Figueiredo; Ricardo Ribeiro Rodrigues; et al. (Mitigation and Adaptation Strategies for Global Change, 2020)

The antidepressant-like effect of guanosine is dependent on GSK-3β inhibition and activation of MAPK/ERK and Nrf2/heme oxygenase-1 signaling pathways - Priscila B. Rosa; Luis E. B. Bettio; Vivian B. Neis; Morgana Moretti; Isabel Werle; Rodrigo B. Leal; Ana Lúcia S. Rodrigues (Purinergic Signalling, 2019)

Applicability of water quality models around the world—a review - Cássia Monteiro da Silva Burigato Costa; Leidiane da Silva Marques; Aleska Kaufmann Almeida; Izabel Rodrigues Leite; Isabel Kaufmann de Almeida (Environmental Science and Pollution Research, 2019)

Ecological restoration as a strategy for mitigating and adapting to climate change: lessons and challenges from Brazil - Mercedes M. C. Bustamante; José Salomão Silva; Aldicir Scariot; Alexandre Bonesso Sampaio; Daniel Luis Mascia; Edenise Garcia; Edson Sano; Geraldo Wilson Fernandes; Giselda Durigan; Iris Roitman; Isabel Figueiredo; Ricardo Ribeiro Rodrigues; et al. (Mitigation and Adaptation Strategies for Global Change, 2019)

(Cyto)genomic and epigenetic characterization of BICR 10 cell line and three new established primary human head and neck squamous cell carcinoma cultures - Ilda P. Ribeiro; Joana M. Rodrigues; Alexandra Mascarenhas; Vanessa Marques; Francisco Caramelo; Maria J. Julião; Thomas Liehr; Joana B. Melo; Isabel M. Carreira (Genes & Genomics, 2019)

Impact of Zinc Stress on Biochemical and Biophysical Parameters in Coffea Arabica Seedlings - Jacqueline Oliveira dos Santos; Cinthia Aparecida Andrade; Kamila Rezende Dázio de Souza; Meline de Oliveira Santos; Isabel Rodrigues Brandão; Jose Donizeti Alves; Iasminy Silva Santos (Journal of Crop Science and Biotechnology, 2019)

Giardia spp. and Cryptosporidium spp. removal efficiency of a combined fixed-film system treating domestic wastewater receiving hospital effluent - Sandra Yamashiro; Mário Luiz Rodrigues Foco; Carolina Ortiz Pineda; Juliana José; Edson Aparecido Abdul Nour; Isabel Cristina Vidal Siqueira-Castro; Regina Maura Bueno Franco (Environmental Science and Pollution Research, 2019)

Extraction and Analysis of Compounds with Antibacterial Potential from the Red Alga Grateloupia turuturu - Isabel Cardoso; João Cotas; Ana Rodrigues; Daniel Ferreira; Nádia Osório; Leonel Pereira (Journal of Marine Science and Engineering, 2019)
Nowadays, the development of new drugs only relies on a small number of molecules and 50% of all existent drugs are extracted or synthetically obtained. This work intends to evaluate the antibacterial potential of the ethanolic and polysaccharide extracts obtained from Grateloupia turuturu and to characterize the composition of the alga’s polysaccharides by FTIR-ATR. We used sequential extraction to obtain the extracts that were tested against S. aureus and E. coli. The ethanolic extracts in E. coli, at the highest concentration used (15 mg mL−1) showed 45.7% (Tetrasporophyte extract) and 55.1% (Carposporophyte extract) of growth reduction and in S. aureus 56.2% (T extract) and 51.8% (C extract). Polysaccharide extracts started showing significant reduction effect on E. coli and S. aureus growth at 7.5 mg mL−1 with a reduction of 54.9% and 39.5%, respectively. At 15 mg mL−1 the reduction observed was 88.5% and 85.4%. The FTIR-ATR allowed to characterize G. turuturu’s polysaccharides concluding that it is composed by a hybrid kappa/iota carrageenan with traces of agar, in both phases of the life cycle. This work allows us to conclude about the antibacterial properties of this alga and the compounds that might be behind this activity, showing that there’s a lot more than a small number of molecules that can be used as natural drugs.

Caste‐ and pesticide‐specific effects of neonicotinoid pesticide exposure on gene expression in bumblebees - Thomas J. Colgan; Isabel K. Fletcher; Andres N. Arce; Richard J. Gill; Ana Ramos Rodrigues; Eckart Stolle; Lars Chittka; Yannick Wurm (Molecular Ecology, 2019)
Social bees are important insect pollinators of wildflowers and agricultural crops, making their reported declines a global concern. A major factor implicated in these declines is the widespread use of neonicotinoid pesticides. Indeed, recent research has demonstrated that exposure to low doses of these neurotoxic pesticides impairs bee behaviours important for colony function and survival. However, our understanding of the molecular‐genetic pathways that lead to such effects is limited, as is our knowledge of how effects may differ between colony members. To understand what genes and pathways are affected by exposure of bumblebee workers and queens to neonicotinoid pesticides, we implemented a transcriptome‐wide gene expression study. We chronically exposed Bombus terrestris colonies to either clothianidin or imidacloprid at field‐realistic concentrations while controlling for factors including colony social environment and worker age. We reveal that genes involved in important biological processes including mitochondrial function are differentially expressed in response to neonicotinoid exposure. Additionally, clothianidin exposure had stronger effects on gene expression amplitude and alternative splicing than imidacloprid. Finally, exposure affected workers more strongly than queens. Our work demonstrates how RNA‐Seq transcriptome profiling can provide detailed novel insight on the mechanisms mediating pesticide toxicity to a key insect pollinator.

Unravelling the antitumoral potential of novel bis(thiosemicarbazonato) Zn(II) complexes: structural and cellular studies - Elisa Palma; Hugo M. Botelho; Goreti Ribeiro Morais; Inês Rodrigues; Isabel Cordeiro Santos; Maria Paula Cabral Campello; Paula Raposinho; Ana Belchior; Susana Sousa Gomes; Maria Fátima Araújo; Isabel Correia; Nadia Ribeiro; et al. (JBIC Journal of Biological Inorganic Chemistry, 2019)

Olive response to potassium applications under different water regimes and cultivars - Isabel Q. Ferreira; Margarida Arrobas; José Moutinho-Pereira; Carlos Correia; M. Ângelo Rodrigues (Nutrient Cycling in Agroecosystems, 2018)

Tauroursodeoxycholic Acid Improves Motor Symptoms in a Mouse Model of Parkinson’s Disease - Alexandra Isabel Rosa; Sara Duarte-Silva; Anabela Silva-Fernandes; Maria João Nunes; Andreia Neves Carvalho; Elsa Rodrigues; Maria João Gama; Cecília Maria Pereira Rodrigues; Patrícia Maciel; Margarida Castro-Caldas (Molecular Neurobiology, 2018)

Global Island Monitoring Scheme (GIMS): a proposal for the long-term coordinated survey and monitoring of native island forest biota - Paulo A. V. Borges; Pedro Cardoso; Holger Kreft; Robert J. Whittaker; Simone Fattorini; Brent C. Emerson; Artur Gil; Rosemary G. Gillespie; Thomas J. Matthews; Ana M. C. Santos; Manuel J. Steinbauer; Christophe Thébaud; et al. (Biodiversity and Conservation, 2018)

Spatial distance and climate determine modularity in a cross‐biomes plant–hummingbird interaction network in Brazil - Andréa Cardoso Araujo; Ana M. Martín González; Brody Sandel; Pietro K. Maruyama; Erich Fischer; Jeferson Vizentin‐Bugoni; Francielle Paulina de Araújo; Aline Góes Coelho; Rogério Rodrigues Faria; Glauco Kohler; Flor Maria Guedes Las‐Casas; Ariadna Valentina Lopes; et al. (Journal of Biogeography, 2018)
Aim We examined the effects of space, climate, phylogeny and species traits on module composition in a cross‐biomes plant–hummingbird network. Location Brazil, except Amazonian region. Methods We compiled 31 local binary plant–hummingbird networks, combining them into one cross‐biomes metanetwork. We conducted a modularity analysis and tested the relationship between species’ module membership with traits, geographical location, climatic conditions and range sizes, employing random forest models. We fitted reduced models containing groups of related variables (climatic, spatial, phylogenetic, traits) and combinations of groups to partition the variance explained by these sets into unique and shared components. Results The Brazilian cross‐biomes network was composed of 479 plant and 42 hummingbird species, and showed significant modularity. The resulting six modules conformed well to vegetation domains. Only plant traits, not hummingbird traits, differed between modules, notably plants’ growth form, corolla length, flower shape and colour. Some modules included plant species with very restricted distributions, whereas others encompassed more widespread ones. Widespread hummingbirds were the most connected, both within and between modules, whereas widespread plants were the most connected between modules. Among traits, only nectar concentration had a weak effect on among‐module connectivity. Main conclusions Climate and spatial filters were the main determinants of module composition for hummingbirds and plants, potentially related to resource seasonality, especially for hummingbirds. Historical dispersal‐linked contingency, or environmental variations not accounted for by the explanatory factors here evaluated, could also contribute to the spatial component. Phylogeny and morphological traits had no unique effects on the assignment of species to modules. Widespread species showed higher within‐ and/or among‐module connectivity, indicating their key role connecting biomes, and, in the case of hummingbirds, communities within biomes. Our results indicate that biogeography and climate not only determine the variation of modularity in local plant–animal networks, as previously shown, but also affect the cross‐biomes network structure.

Comparative population biology and reproduction of two sympatric crabs (Grapsidae) on Azores cobble beaches - Tarso De Menezes Macedo Costa; Nuno Miguel da Silva Ascensão Vaz Álvaro; Armindo Dos Santos Rodrigues; Ana Isabel De Melo Azevedo Neto; José Manuel Viegas Oliveira Neto Azevedo (Invertebrate Reproduction & Development, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Dendropsophin 1, a novel antimicrobial peptide from the skin secretion of the endemic Colombian frog Dendropsophus columbianus - Luz Elena Triana-Vidal; Mariana Souza Castro; Osmindo Rodrigues Pires Júnior; Alice Cunha Morales Álvares; Sonia Maria de Freitas; Wagner Fontes; Jimmy Alexander Guerrero Vargas; Jorge Alberto Zúñiga-Baos; Isabel de Fátima Correia Batista; Philippe Grellier; Sébastien Charneau (Natural Product Research, 2018)

Structural and physiological responses of Halodule wrightii to ocean acidification - Geniane Schneider; Paulo Antunes Horta; Emiliano Nicolas Calderon; Clovis Castro; Adalto Bianchini; Camilla Reis Augusto da Silva; Isabel Brandalise; José Bonomi Barufi; João Silva; Ana Claudia Rodrigues (Protoplasma, 2018)

First Report on vanA-Enterococcus faecalis Recovered from Soils Subjected to Long-Term Livestock Agricultural Practices in Azores Archipelago - Vanessa Silva; Fernando Peixoto; Gilberto Igrejas; Carolina Parelho; Patrícia Garcia; Isabel Carvalho; Margarida Sousa; José Eduardo Pereira; Armindo Rodrigues; Patrícia Alexandra Curado Quintas D Poeta (International Journal of Environmental Research, 2018)

Life paths of patients with transthyretin-related familial amyloid polyneuropathy Val30Met: a descriptive study - Alice Lopes; Alexandra Sousa; Isabel Fonseca; Margarida Branco; Carla Rodrigues; Teresa Coelho; Jorge Sequeiros; Paula Freitas (Journal of Community Genetics, 2018)

Global patterns of interaction specialization in bird–flower networks - Thais B. Zanata; Bo Dalsgaard; Fernando C. Passos; Peter A. Cotton; James J. Roper; Pietro K. Maruyama; Erich Fischer; Matthias Schleuning; Ana M. Martín González; Jeferson Vizentin‐Bugoni; Donald C. Franklin; Stefan Abrahamczyk; et al. (Journal of Biogeography, 2017)
Aim Among the world's three major nectar‐feeding bird taxa, hummingbirds are the most phenotypically specialized for nectarivory, followed by sunbirds, while the honeyeaters are the least phenotypically specialized taxa. We tested whether this phenotypic specialization gradient is also found in the interaction patterns with their floral resources. Location Americas, Africa, Asia and Oceania/Australia. Methods We compiled interaction networks between birds and floral resources for 79 hummingbird, nine sunbird and 33 honeyeater communities. Interaction specialization was quantified through connectance ( C ), complementary specialization ( H 2 ′), binary ( Q B ) and weighted modularity ( Q ), with both observed and null‐model corrected values. We compared interaction specialization among the three types of bird–flower communities, both independently and while controlling for potential confounding variables, such as plant species richness, asymmetry, latitude, insularity, topography, sampling methods and intensity. Results Hummingbird–flower networks were more specialized than honeyeater–flower networks. Specifically, hummingbird–flower networks had a lower proportion of realized interactions (lower C ), decreased niche overlap (greater H 2 ′) and greater modularity (greater Q B ). However, we found no significant differences between hummingbird– and sunbird–flower networks, nor between sunbird– and honeyeater–flower networks. Main conclusions As expected, hummingbirds and their floral resources have greater interaction specialization than honeyeaters, possibly because of greater phenotypic specialization and greater floral resource richness in the New World. Interaction specialization in sunbird–flower communities was similar to both hummingbird–flower and honeyeater–flower communities. This may either be due to the relatively small number of sunbird–flower networks available, or because sunbird–flower communities share features of both hummingbird–flower communities (specialized floral shapes) and honeyeater–flower communities (fewer floral resources). These results suggest a link between interaction specialization and both phenotypic specialization and floral resource richness within bird–flower communities at a global scale.

Evaluation of stability and validation of reference genes for RT-qPCR expression studies in rice plants under water deficit - Priscila Ariane Auler; Letícia Carvalho Benitez; Marcelo Nogueira do Amaral; Isabel Lopes Vighi; Gabriela dos Santos Rodrigues; Luciano Carlos da Maia; Eugenia Jacira Bolacel Braga (Journal of Applied Genetics, 2017)

A case of multiple gastrointestinal stromal tumors caused by a germline KIT gene mutation (p.Leu576Pro) - Rita Vale Rodrigues; Filipa Santos; João Pereira da Silva; Inês Francisco; Isabel Claro; Cristina Albuquerque; Maria Manuel Lemos; Manuel Limbert; António Dias Pereira (Familial Cancer, 2017)

Caffeine Reverts Memory But Not Mood Impairment in a Depression-Prone Mouse Strain with Up-Regulated Adenosine A2A Receptor in Hippocampal Glutamate Synapses - Nuno J. Machado; Ana Patrícia Simões; Henrique B. Silva; Ana Paula Ardais; Manuella P. Kaster; Pedro Garção; Diana I. Rodrigues; Daniela Pochmann; Ana Isabel Santos; Inês M. Araújo; Lisiane O. Porciúncula; Ângelo R. Tomé; et al. (Molecular Neurobiology, 2017)

Phylogenetic analysis of rabies virus isolated from canids in North and Northeast Brazil - Débora Nunes de Souza; Pedro Carnieli; Carla Isabel Macedo; Rafael de Novaes Oliveira; Helena Beatriz de Carvalho Ruthner Batista; Adriana Candido Rodrigues; Patricia Mariano Cruz Pereira; Samira Maria Achkar; Luiz Fernando Pereira Vieira; Juliana Galera Castilho Kawai (Archives of Virology, 2017)

Soil contamination assessment for Pb, Zn and Cd in a slag disposal area using the integration of geochemical and microbiological data - Mariana Consiglio Kasemodel; Jacqueline Zanin Lima; Isabel Kimiko Sakamoto; Maria Bernadete Amancio Varesche; Julio Cesar Trofino; Valéria Guimarães Silvestre Rodrigues (Environmental Monitoring and Assessment, 2016)

Correlation of proline content and gene expression involved in the metabolism of this amino acid under abiotic stress - Letícia Carvalho Benitez; Isabel Lopes Vighi; Priscila Ariane Auler; Marcelo Nogueira do Amaral; Gabriela Peres Moraes; Gabriela dos Santos Rodrigues; Luciano Carlos da Maia; Ariano Martins de Magalhães Júnior; Eugenia Jacira Bolacel Braga (Acta Physiologiae Plantarum, 2016)

Agmatine, by Improving Neuroplasticity Markers and Inducing Nrf2, Prevents Corticosterone-Induced Depressive-Like Behavior in Mice - Andiara E. Freitas; Javier Egea; Izaskun Buendia; Vanessa Gómez-Rangel; Esther Parada; Elisa Navarro; Ana Isabel Casas; Aneta Wojnicz; José Avendaño Ortiz; Antonio Cuadrado; Ana Ruiz-Nuño; Ana Lúcia S. Rodrigues; et al. (Molecular Neurobiology, 2016)

Enhancing the biodiesel manufacturing process by use of glycerin to produce hyacinth fragrance - Cauê A. C. Silva; Flávia C. A. Figueiredo; Raphael Rodrigues; Mirela I. Sairre; Maraisa Gonçalves; Ines Matos; Isabel M. Fonseca; Dalmo Mandelli; Wagner A. Carvalho (Clean Technologies and Environmental Policy, 2016)

First report on Meloidogyne chitwoodi hatching inhibition activity of essential oils and essential oils fractions - Jorge Miguel Silva Faria; Inês Sena; Bruno Ribeiro; Ana Margarida Rodrigues; Carla Maria Nobre Maleita; Isabel Abrantes; Richard Bennett; Manuel Mota; Ana Cristina da Silva Figueiredo (Journal of Pest Science, 2016)

Long‐term elevated air [ CO 2 ] strengthens photosynthetic functioning and mitigates the impact of supra‐optimal temperatures in tropical Coffea arabica and C. canephora species - Weverton P. Rodrigues; Madlles Q. Martins; Ana S. Fortunato; Ana P. Rodrigues; José N. Semedo; Maria C. Simões‐Costa; Isabel P. Pais; António E. Leitão; Filipe Colwell; Luis Goulao; Cristina Máguas; Rodrigo Maia; et al. (Global Change Biology, 2016)
The tropical coffee crop has been predicted to be threatened by future climate changes and global warming. However, the real biological effects of such changes remain unknown. Therefore, this work aims to link the physiological and biochemical responses of photosynthesis to elevated air [ CO 2 ] and temperature in cultivated genotypes of C offea arabica L. (cv. Icatu and IPR 108) and Coffea canephora cv. Conilon CL 153. Plants were grown for ca. 10 months at 25/20 °C (day/night) and 380 or 700 μl CO 2 l −1 and then subjected to temperature increase (0.5 °C day −1 ) to 42/34 °C. Leaf impacts related to stomatal traits, gas exchanges, C isotope composition, fluorescence parameters, thylakoid electron transport and enzyme activities were assessed at 25/20, 31/25, 37/30 and 42/34 °C. The results showed that (1) both species were remarkably heat tolerant up to 37/30 °C, but at 42/34 °C a threshold for irreversible nonstomatal deleterious effects was reached. Impairments were greater in C. arabica (especially in Icatu) and under normal [ CO 2 ]. Photosystems and thylakoid electron transport were shown to be quite heat tolerant, contrasting to the enzymes related to energy metabolism, including RuBis CO , which were the most sensitive components. (2) Significant stomatal trait modifications were promoted almost exclusively by temperature and were species dependent. Elevated [ CO 2 ], (3) strongly mitigated the impact of temperature on both species, particularly at 42/34 °C, modifying the response to supra‐optimal temperatures, (4) promoted higher water‐use efficiency under moderately higher temperature (31/25 °C) and (5) did not provoke photosynthetic downregulation. Instead, enhancements in [ CO 2 ] strengthened photosynthetic photochemical efficiency, energy use and biochemical functioning at all temperatures. Our novel findings demonstrate a relevant heat resilience of coffee species and that elevated [ CO 2 ] remarkably mitigated the impact of heat on coffee physiology, therefore playing a key role in this crop sustainability under future climate change scenarios.

Changes in the salivary protein profile of morbidly obese women either previously subjected to bariatric surgery or not - Elsa Lamy; Carla Simões; Lénia Rodrigues; Ana Rodrigues Costa; Rui Vitorino; Francisco Amado; Célia Antunes; Isabel do Carmo (Journal of Physiology and Biochemistry, 2015)

Early-maturing annual legumes: an option for cover cropping in rainfed olive orchards - M. Ângelo Rodrigues; Paulo Dimande; Ermelinda L. Pereira; Isabel Q. Ferreira; Sara Freitas; Carlos M. Correia; José Moutinho-Pereira; Margarida Arrobas (Nutrient Cycling in Agroecosystems, 2015)

Eastern equine encephalitis cases among horses in Brazil between 2005 and 2009 - Rafael de Novaes Oliveira; Keila Iamamoto; Maria Luana Cristiny Rodrigues Silva; Samira Maria Achkar; Juliana Galera Castilho; Ekaterina Durymanova Ono; Renata Spinelli Vaz Lobo; Paulo Eduardo Brandão; Pedro Carnieli; Maria Luiza Carrieri; Ivanete Kotait; Carla Isabel Macedo (Archives of Virology, 2014)

Physiological and biochemical impacts of magnesium-deficiency in two cultivars of coffee - Dayane Meireles da Silva; Isabel Rodrigues Brandão; Jose Donizeti Alves; Meline Oliveira de Santos; Kamila Rezende Dázio de Souza; Helbert Rezende Oliveira de Silveira (Plant and Soil, 2014)

Insights into the mechanisms underlying the antiproliferative potential of a Co(II) coordination compound bearing 1,10-phenanthroline-5,6-dione: DNA and protein interaction studies - Daniel V. Luís; Joana Silva; Ana Isabel Tomaz; Rodrigo F. M. de Almeida; Miguel Larguinho; Pedro V. Baptista; Luísa M. D. R. S. Martins; Telma F. S. Silva; Pedro M. Borralho; Cecília M. P. Rodrigues; António S. Rodrigues; Armando J. L. Pombeiro; et al. (JBIC Journal of Biological Inorganic Chemistry, 2014)

Kelps across the portuguese coast: evidence of top-down and bottom-up influences - Franco Joao; Wernberg Thomas; Bertocci Iacopo; Arenas Francisco; Martínez Brezo; Duarte Pedro; Jacinto David; Vasco-Rodrigues Nuno; Sousa-Pinto Isabel; Tuya Fernando (Frontiers in Marine Science, 2014)

Isolation and characterization of rice (Oryza sativa L.) E3-ubiquitin ligase OsHOS1 gene in the modulation of cold stress response - Tiago Lourenço; Helena Sapeta; Duarte D. Figueiredo; Mafalda Rodrigues; André Cordeiro; Isabel A. Abreu; Nelson J. M. Saibo; M. Margarida Oliveira (Plant Molecular Biology, 2013)

Geno- and Cyto-toxicity in Free-Living Rodent Mus spretus Exposed to Simulated Onshore Oil Spill - Flavio Manoel Rodrigues da Silva Júnior; Rita Isabel Monarca; Deodália Dias; Maria da Graça Ramalhinho; Maria da Luz Mathias; Ana Luíza Muccillo-Baisch (Bulletin of Environmental Contamination and Toxicology, 2013)

Bethesda criteria for microsatellite instability testing: impact on the detection of new cases of Lynch syndrome - Miguel Serrano; Pedro Lage; Sara Belga; Bruno Filipe; Inês Francisco; Paula Rodrigues; Ricardo Fonseca; Paula Chaves; Isabel Claro; Cristina Albuquerque; António Dias Pereira (Familial Cancer, 2012)

Reproductive isolation between diploid and tetraploid cytotypes of Libidibia ferrea (= Caesalpinia ferrea) (Leguminosae): ecological and taxonomic implications - Laís Angélica Borges; Luiz Gustavo Rodrigues Souza; Marcelo Guerra; Isabel Cristina Machado; Gwilym P. Lewis; Ariadna Valentina Lopes (Plant Systematics and Evolution, 2012)

Familial colorectal cancer type X syndrome: two distinct molecular entities? - Inês Francisco; Cristina Albuquerque; Pedro Lage; Hélio Belo; Inês Vitoriano; Bruno Filipe; Isabel Claro; Sara Ferreira; Paula Rodrigues; Paula Chaves; Carlos Nobre Leitão; António Dias Pereira (Familial Cancer, 2011)

Haplotypes of the bovine IgG2 heavy gamma chain in tick-resistant and tick-susceptible breeds of cattle - Wanessa Araújo Carvalho; Patricia Ianella; Frederico G. C. Arnoldi; Alexandre Rodrigues Caetano; Sandra Regina Maruyama; Beatriz Rossetti Ferreira; Luís Henrique Andreucci Conti; Marcia Ramos Monteiro da Silva; José Otavio F. Paula; Antonio Augusto Mendes Maia; Isabel K. Ferreira de Miranda Santos (Immunogenetics, 2011)

A-type inclusion bodies: a factor influencing cowpox virus lesion pathogenesis - Juliana Almeida Leite; Flávio Guimarães da Fonseca; Giliane de Souza Trindade; Jônatas Santos Abrahão; Rosa Maria Esteves Arantes; Camila Megale de Almeida-Leite; João Rodrigues dos Santos; Maria Isabel Maldonado Coelho Guedes; Bergmann Morais Ribeiro; Cláudio Antônio Bonjardim; Paulo César Peregrino Ferreira; Erna Geessien Kroon (Archives of Virology, 2011)

Using taxonomically unbiased criteria to prioritize resource allocation for oceanic island species conservation - José L. Martín; Pedro Cardoso; Manuel Arechavaleta; Paulo A. V. Borges; Bernardo F. Faria; Cristina Abreu; António F. Aguiar; José A. Carvalho; Ana C. Costa; Regina T. Cunha; Francisco M. Fernandes; Rosalina Gabriel; et al. (Biodiversity and Conservation, 2010)

GSTpi Expression in MPTP-Induced Dopaminergic Neurodegeneration of C57BL/6 Mouse Midbrain and Striatum - Margarida Castro-Caldas; Andreia Neves Carvalho; Isabel Peixeiro; Elsa Rodrigues; Maria Celeste Lechner; Maria João Gama (Journal of Molecular Neuroscience, 2009)

Establishment of a Tumour Bank: the experience of the Department of Pathology of Hospital S. João (Porto, Portugal) - Marta Rodrigues; Isabel Vitó; Raquel Santos; Joel Paiva; Patrícia Pontes; Paula Silva; Fátima Carneiro (Cell and Tissue Banking, 2009)

Identification of an arsenic resistance mechanism in rhizobial strains - Paula Sá-Pereira; Mónica Rodrigues; Isabel Videira e Castro; Fernanda Simões (World Journal of Microbiology and Biotechnology, 2007)

Superoxide reduction by Archaeoglobus fulgidus desulfoferrodoxin: comparison with neelaredoxin - João V. Rodrigues; Lígia M. Saraiva; Isabel A. Abreu; Miguel Teixeira; Diane E. Cabelli (JBIC Journal of Biological Inorganic Chemistry, 2007)

Desulfovibrio gigas ferredoxin II: redox structural modulation of the [3Fe–4S] cluster - Pedro M. Rodrigues; Anjos L. Macedo; Brian J. Goodfellow; Isabel Moura; José J. G. Moura (JBIC Journal of Biological Inorganic Chemistry, 2006)

The Influence of the North Atlantic Oscillation on Rainfall Triggering of Landslides near Lisbon - Ricardo M. Trigo; José L. Zêzere; Maria L. Rodrigues; Isabel F. Trigo (Natural Hazards, 2005)

The solution structure of a [3Fe-4S] ferredoxin: oxidised ferredoxin II from Desulfovibrio gigas - B. J. Goodfellow; A. L. Macedo; Pedro Rodrigues; Isabel Moura; Victor Wray; José J. G. Moura (JBIC Journal of Biological Inorganic Chemistry, 1999)